Effect of Existence Needs, Relatedness Needs, and Growth Needs on Employee Work Productivity - Lilis Sulastri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the effect of Motivation (E.R.G Needs) on Employee Work Productivity, either partially or simultaneously, on employees of the National Aeronautics and Space Agency (LAPAN) Garut Selatan Office. The research method used is descriptive and verification research methods with a quantitative approach. The sampling technique in this study used a non-probability sample with a saturated sample technique, namely 100 employees of the South Garut South Garut National Aeronautics and Space Agency (LAPAN). In the t-test, t count > t table equals 2.209 > 1.9847, with a significance level of 0.005 < 0.05, and ttable equals 2.209 > 1.9847. To sum up, personal needs have an impact on the amount of work people are able to get done t count > t table is 2, > 1.9847 and 0.000 < 0.05 is significant, therefore it may be argued that Relatedness Needs impact Work Productivity. To conclude that growth affects work productivity, we can look at the data and see that the values of t count > t table are 2, > 1.9847 and 0.000 < 0.05. This shows that Existence Needs, Relatedness Needs, and Growth Needs all have an impact on Work Productivity, and the significant value of 0.000 > 0.05 can be deduced from the results of the F test. An R square of 0.299, or 29.9 percent, was derived from the coefficient of determination analysis. Existence, Relatedness, and Growth Needs Affect Work Productivity by 29.9%, whereas Variables Not Examined Affect Work Productivity by 70.1% the remaining.